Toxic Relationship Dalam Pacaran Pada Mahasiswa FIS Universitas Negeri Jakarta - Witri Azkia; Desy Safitri; Saipiatuddin Saipiatuddin (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2024)
Toxic relationships in dating are those that do not contribute positively to the development of both parties involved. Toxic relationships often stem from dominance exerted by one party, leading the other to feel oppressed or uncomfortable within the relationship. This research aims to identify toxic relationships in dating among students at the Faculty of Social Sciences, Universitas Negeri Jakarta. The research method employed is descriptive, with a quantitative approach, utilizing questionnaire surveys and interviews as data collection techniques. The sample size for this research comprised 63 respondents selected through purposive sampling. The findings of this study indicate that the most dominant form of toxic relationship in dating among students at the Faculty of Social Sciences, Universitas Negeri Jakarta, is possessive behavior, such as monitoring and scrutinizing every move of the partner, lack of trust, or frequent suspicion of the partner as a result of excessive jealousy. These behaviors reflect a lack of trust and an excessive level of control over the partner, resulting in an unhealthy environment where one party feels bound and constrained by the unreasonable desires of the partner.